1990
DOI: 10.1007/bf00973749
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-l-carnitine as a precursor of acetylcholine

Abstract: Synthesis of [3H]acetylcholine from [3H]acetyl-L-carnitine was demonstrated in vitro by coupling the enzyme systems choline acetyltransferase and carnitine acetyltransferase. Likewise, both [3H] and [14C] labeled acetylcholine were produced when [3H]acetyl-L-carnitine and D-[U-14C] glucose were incubated with synaptosomal membrane preparations from rat brain. Transfer of the acetyl moiety from acetyl-L-carnitine to acetylcholine was dependent on concentration of acetyl-L-carnitine and required the presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 16 publications
0
64
0
2
Order By: Relevance
“…The cognition-improving effect of ALCAR may also be caused in part by the donation of an acetyl group for the synthesis of the neurotransmitter acetylcholine through choline acetyltransferase and carnitine acetyltransferase (17,71,72). Low acetylcholine levels in certain brain regions are associated with age-related cognitive dysfunction, including AD (73).…”
Section: Discussionmentioning
confidence: 99%
“…The cognition-improving effect of ALCAR may also be caused in part by the donation of an acetyl group for the synthesis of the neurotransmitter acetylcholine through choline acetyltransferase and carnitine acetyltransferase (17,71,72). Low acetylcholine levels in certain brain regions are associated with age-related cognitive dysfunction, including AD (73).…”
Section: Discussionmentioning
confidence: 99%
“…ALC is involved in cognitive functions and neuronal bioenergetics mechanisms with both short-and long-term treatments in rats [14], and there is some experimental evidence that ALC might also have antiaging effects and cardioprotective activity [11,15,16], restoring the age-associated decline of learning and memory in old animals [17]. Several studies have also indicated that ALC potentiates the cholinergic transmission and provides a possible tool for Alzheimer's disease (AD) treatment [18]. A recent study suggests that supplementation with ALC improves spatial working memory deficits, reduces oxidative stress, and inhibits apoptotic cascade induced by hypoxia [19].…”
Section: Introductionmentioning
confidence: 98%
“…L-karnityna uczestniczy również w przekształcaniu acetylo-koenzymu A (acetylo-CoA) do acetylokarnityny i koenzymu A (CoA), co w efekcie zwiększa dostępność CoA potrzebnego do dekarboksylacji oksydacyjnej pirogronianu w cyklu Krebsa. W układzie nerwowym acetylokarnityna jest donorem grup acetylowych niezbędnych do tworzenia acetylocholiny [17,18]. Poza rolą w utlenianiu kwasów tłuszczowych L-karnityna bierze udział w metabolizmie aminokwasów (leucyny, izoleucyny i waliny) oraz w chelatowaniu takich pierwiastków jak żelazo, ołów i kadm, ułatwiając ich transport oraz usuwanie ich nadmiaru [1].…”
Section: +unclassified